Potential corruption in the stunting alleviation program: A cost-benefit analysis of local food-based feeding program - Adryan Kusumawardhana; Syahdu Winda; Kunto Ariawan (Komisi Pemberantasan Korupsi, 2024)
In poor rural areas, stunting threatens the health and nutrition of children aged five and under. Despite persistent efforts, Indonesia's stunting rate remains high. The primary objective of this study is to assess the effectiveness of programs designed to mitigate stunting. The e-PPGBM data analysis investigates whether there is a connection between potential corruption and the allocation of funds for a nutritional program in 2023. This study uses cost-benefit analysis to compare government program budgets with the potential benefits of taxable income as an indicator of potential state financial losses. The study's findings indicate that implementing local food-based feeding programs will have a favorable impact on state revenue. However, budget limitations on the program preclude interaction with the entire target group and the collection of substantially higher income tax, which might cost the state in the future. Furthermore, the study found the potential for financial losses for the state due to inaccurate aid recipient selection, which could cause the program to fall short of its intended results. From an academic perspective, this study advises health sector government officials to rely on data and evidence to meet program objectives without harming state budgets.